Steering Towards Low-Carbon Road Freight Transport Through Policies - The Case of Oslo - Jystad,Torstein Clausen (IIIEE Masters Thesis, 2017)
The primary purpose of this thesis is to assess policy measures promoting the uptake and use of low-carbon technologies in urban road freight transport (URFT) in Oslo, Norway. This sector has historically received little attention compared to passenger and public transport, but contribute to significant greenhouse gas (GHG) emissions, noise, and other negative health effects. Low-carbon vehicles in this research are referred to as electric and hydrogen vehicles, which could help mitigate these effects. To promote their uptake and use, policy measures must be implemented and synchronized with expectations from various stakeholders directly and indirectly impacting URFT. This is important to ensure effective results. Findings were collected through a literature review and semi-structured interviews with, among others, authorities, freight operators, original equipment manufacturers (OEM’s), and research organisations. Findings suggest several policy measures are needed to promote the uptake and use of low-carbon freight vehicles, most urgently in the category of fiscal measures, and facilitation of low-carbon infrastructure. Also, toll roads, fuel taxes and various subsidy schemes were stressed as necessary to reduce high costs for low-carbon URFT vehicles, while zero/low-emission zones received overall high encouragement. Furthermore, green public procurements were generally considered positively among all interviewees to help create an early market. Stricter demands and prolonged tendering processes should be considered in these processes. In assessing individual policy measures towards the criteria of effort, effectiveness, and acceptability, areas for improvement were identified. For facilitation of low-carbon infrastructure, effectiveness was found to likely improve if financial contributions exceed current mandates, targeting early adopters in urban areas, and offering operational support. Other challenges in Oslo’s URFT were linked to the need for authorities to clearly communicate what fuel propulsions are prioritised. Also, authorities should sometimes disregard the principle of technology neutrality, particularly relevant when supporting low-carbon technologies in an early phase. Further, the lack of delegating responsibility of URFT to a specific authority were identified as a drawback. Various levels and overlapping powers within political institutions ultimately begged the question of what specific body feel responsible for URFT. As such, creating a city logistics plan for Oslo should be the primary step, delegated to a specific agency or ministry both locally and nationally. Future research should focus on approaches between cities and best practices as to managing URFT. The sector is still in its infancy for what concerns political attention, on the backdrop of higher demand, emissions of GHG’s, other harmful pollutants, and negative side-effects such as noise.
Keywords: Urban freight; low-carbon technologies; electric trucks; hydrogen trucks; policy measures